PEMANFAATAN CITRA LANDSAT 7 ETM+ UNTUK DETEKSI PERUBAHAN PENGGUNAAN LAHAN PASCA BENCANA ERUPSI GUNUNG MERAPI TAHUN 2010 - , RASTIKA WIDIASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi eruption disaster in 2012 is the biggest eruption during the last 100 years. Natural phenomena caused the significant landuse changing around Yogyakarta and Jateng. The landuse changing post merapi eruption should be identified. To analyze the changing, landsat 7 ETM+ imagery can be used.The landuse changing post 2010 merapi eruption can be identified by using Landsat 7 ETM+ mode SLC-off. Landsat 7 ETM+ mode SLC-off with path 120 and row 65 year 2009 and 2012 are involved in this research. Broken sensor which cause the Remote Sensing Imagery that produced by Landsat 7 ETM+ satellite is resolved with gapfilling process. By doing this, the information contained in the image can be extracted. Through the imagery pre-processing completed with gapfilling, image compossit, radiometric correction, geometric correction, and imagery cropping, this research project is done. There were several stages to process. These were the stages: choosing the training area, statistic calculating for the training area, and detecting the changes. This project using minimun distance digital classification. Overall accuracy for Landsat 7 ETM+ year 2009 image is 88,9% and for year 2012 image is 89,6%. Change detection analisys is proved that there are landuse changing on 2208,463 kms project area. Urban area is increasing 70,124 kms, agriculture field is increasing 481,930 kms, water landuse is increasing 23,292 kms, the width of volcanic material is decreasing 6,276 kms, forest is decreasing 199,856 kms, farm is decreasing 82,905 kms, sand area is decreasing 27,736 kms, road is decreasing 1,776 kms, and for open area is decreasing 268,148 kms. (kms= kilometers square)